Pre-drinking motives are directly associated with alcohol-related consequences even after adjusting for alcohol use on a given night: A consequence-specific analysis. (February 2023) - Labhart, Florian; Smit, Koen; Anderson-Luxford, Dan; Kuntsche, Emmanuel
Highlights: Pre-drinking motives are associated with consequences over and above alcohol use. General drinking motives are not associated with night-level consequences. Risky sex is associated with higher 'conviviality' pre-drinking motives. Blackout is associated with lower 'conviviality' pre-drinking motives. Drunk driving is more likely among males who pre-drink for 'fun/intoxication' motives. Abstract: Introduction: Pre-drinking motives (PDM) are linked with different characteristics of pre-drinking occasions (e.g., fast-paced drinking, socializing, moving across locations) that are potentially related to adverse night-level consequences. This study examines the direct associations of three PDM dimensions (fun/intoxication, facilitation, and conviviality) with the occurrence of five consequences (hangover, impaired driving, blackout, risky sex, fight/injury) over and above amounts of alcohol consumed that night. Methods: A sample of 138 young adult nightlife goers (55.1 % men, M age = 19.0 SD = 2.4) in Switzerland reported PDM at baseline, and subsequently reported night-level alcohol use and consequences the next morning on 12.1 weekend nights on average (N = 1, 663 participant-nights). Correlational analyses and multilevel logistic regression models assessed associations between PDM and night-level consequences. Results: After adjusting for amounts consumed, age, sex and monthly pre-drinking frequency, conviviality PDM were associated with higher odds of risky sex (OR = 2.68) and lower odds of blackout (OR = 0.57) while fun/intoxication PDM were associated with lower odds of risky sex (OR = 0.35). Interaction analyses per gender showed that fun/intoxication PDM were associated with lower odds of impaired driving among women (OR = 0.25). Results remained the same when adjusting for general drinking motives, which were not associated with night-level consequences. Conclusion: PDM might better capture risk factors for experiencing night-level consequences than general drinking motives. Preventive intervention should make young people aware that pre-drinking is not only associated with higher amounts of alcohol consumed, but also with increased risks of specific night-level consequences, including blackouts and risky sexual behaviors, depending on the level of endorsement of each PDM.